Remarks on elements of Japanese landscape and their geotouristic attractiveness - Myga-Piątek, Urszula (Geotourism/Geoturystyka, 2025)
For western tourists Japan is a mysterious country. That mystery was further increased by relatively long-lasting political isolationism, which consequently resulted in tourism isolationism. With tragic events – a 9-magnitude earthquake and a resulting gigantic tsunami, reaching 10 meters in height (11.03.2011) inthe background, the author will analyze the geotourist potential of Japan. It can be predicted that, paradoxically, the strong earthquake and tsunami will soon result in an increased inflow of tourists. That might be related to the development of many new forms of geotourism, among which dark tourism became most and most popular. In this highly urbanized country, the geological heritage creates relict landscapes which could be referred to as quasi-natural.There are very interesting from a tourist point of view. The article was based on the author’s own observations during her study trip around Japan in May, 2009. The journey around picturesque and to a great extent wild, as for Japan, spots of Shikoku and Honshu, inspired the author to present a few notes regarding thegeotourist attractiveness of that country. This is an attempt to assess the environmental potential from the point of view of an European tourist.